Associations between Macrophyte Life Forms and Environmental and Morphometric Factors in a Large Sub-tropical Floodplain - Schneider, Berenice; Cunha, Eduardo R.; Marchese, Mercedes; Thomaz, Sidinei M. (Frontiers in Plant Science, 2018)
Macrophyte assemblages are composed of species with different life forms and various ecological functions. Our aim was to investigate the potential environmental determinants of changes in the biomass of individual life forms and of the composition of the macrophyte assemblage in terms of life forms diversity. We sampled 23 waterbodies at low and high water levels in the Middle Paraná River floodplain. Macrophyte biomass samples were collected and classified in terms of life forms. We performed a redundancy analysis using the biomass of the various life forms to assess the importance of environmental variables to the composition of macrophyte life forms. Linear regressions were applied to investigate the environmental determinants of the biomasses of individual life forms. The degree of connectivity and the combination of depth, hydrology and nitrate were the main determinants of the composition in terms of life forms. The biomass of each individual life form was explained by different combinations of environmental variables, but the connectivity was the most important one. Our study shows that groups of species with similar life forms respond to environmental factors in particular ways, which might alter the biomass composition of life forms. Given that the ecosystem functioning depends on the functional characteristics of local communities, our findings about the relation between environmental changes and the community composition in terms of life forms (or functional composition) can be a helpful tool for predicting changes on ecosystem processes (such as nutrient cycling) against possible future scenarios.